2014
DOI: 10.1177/0269216314522318
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of palliative care needs by family physicians: A qualitative study of barriers and facilitators from the perspective of family physicians, community nurses, and patients

Abstract: The current practice of palliative care in Belgium is far from the presently considered ideal palliative care approaches. Facilitators such as proactive communication and communication tools could contribute to the development of guidelines for family physicians and policymakers in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(139 citation statements)
references
References 32 publications
2
135
0
2
Order By: Relevance
“…Furthermore the relief experienced by families when the hospital admission finally occurred indicated a level of anxiety for caregivers. Worsening and unexplained symptoms and anxiety (30), indeed one study has described as Anxieties about remaining at home when problems, such as unbearable pain, occur can leave patients feeling frightened and insecure (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the relief experienced by families when the hospital admission finally occurred indicated a level of anxiety for caregivers. Worsening and unexplained symptoms and anxiety (30), indeed one study has described as Anxieties about remaining at home when problems, such as unbearable pain, occur can leave patients feeling frightened and insecure (31).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests there is something unique about being in hospital that might be difficult to replicate in the home setting. A recent study by Beernaert et al (31) explored barriers and facilitators to the early identification by general practitioners of palliative care needs. They found that patients often viewed their hospital physicians as being more capable than their general practitioner when dealing with specific manifestations of their illnessThe authors found that general practitioners are less likely to be involved when patient are receiving curative or life prolonging treatment and find it easier to identify palliative care needs in the last weeks of life when prognosis is clearer (31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, feeling incompetent to deal with dying patients might prevent family physicians from taking responsibility for keeping the patient at home or to being available to them. That family physicians are more familiar with cancer end-of-life trajectories 43,44 might also partially explain why cancer patients are more likely to die at home or less likely to die in hospital, compared with patients dying of other causes. 3,4,14,45,46 Improving competencies and attitudes through adequate end-of-life care training therefore seems to be essential to reducing the number of end-of-life hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, awareness and acceptance of palliative care as an emancipated, helpful discipline in lung cancer beyond end-of-life care may be lacking in patients, caregivers and professionals [135][136][137]. WARD et al [138] entitled their survey study "Collaborating or co-existing", highlighting appreciation and barriers in medical oncologists towards palliative care services.…”
Section: Barriers For Integration Of Palliative Care Into Routine Lunmentioning
confidence: 99%